A Stretchable Kirigami‐Inspired Self‐Powered Electroactive Sensor for Tensile Strain and Torsion Sensing. Issue 4 (16th November 2021) - Lee, Jai-Hua; Chee, Pei-Song; Lim, Eng-Hock; Low, Jen-Hahn; Nguyen, Nam-Trung
Abstract : Electroactive polymer has a great potential to be employed for making a self‐powered sensor due to the ionic movement of the mobile cation that exists in the polymer structure itself. However, applying an electroactive‐based sensor as wearable gadget can be challenging due to its limited detection range and nonconformity. Inspired by the Kirigami structure, herein, it has been demonstrated that a self‐powered electroactive‐based sensor with improved conformality. It has been found that the Kirigami structure can enhance the sensor sensitivity significantly. The sensor exhibited high sensitivity to a uniaxial strain deformation with more than 300% sensitivity and a broad sensing range of up to 80% strain. In addition to being able to detect the uniaxial strain, the Kirigami‐patterned sensor also has good torsion and mixed torsion–strain dependent properties, making it a good multifunctional sensor. As a proof‐of‐concept demonstration for applications in monitoring human activities, it has been successfully demonstrated that the proposed Kirigami‐patterned sensor is able to monitor wrist movements and respiration rate. Notably, this Kirigami‐patterned electroactive‐based sensor has significantly broadened the application of electroactive polymer on advanced wearable electronics. Abstract : Herein, integration of Kirigami cutting structure to an electroactive polymer has been done for the first time. The optimized Kirigami‐patterned soft sensor exhibits significantly tolerable strain level up to 80%, in addition to its torsion sensing capability. The soft sensor shows conformal contact around curve surfaces when applied as a wearable sensor.